Development and In Vitro Evaluation of Oral Capsules from Antiaris: A Convenient Substitute for Peripheral Neuropathy - Mary-Ann Archer; Doris Kumadoh; Samuel Nii-Bortier Gaizer; Adelaide Mensah; Jonathan Jato; Micheal Odoi Kyene; Susana Oteng Mintah; Genevieve Naana Yeboah; Paul kwesi Sodzi; Ofosua Adi-Dako (Hindawi Limited, 2022)
Antiaris is a monoherbal decoction produced by the Centre for Plant Medicine Research (CPMR), Mampong-Akuapem, Ghana. It is prepared from the stem bark of Antiaris africana Engl. (Moraceae), prescribed, and dispensed to patients for the management of nervous disorders. This current formulation presents notable challenges in patients' adherence to treatment regimen due to its bulkiness and bitterness. These challenges have resulted in a decrease in therapeutic outcome. This study sought to transform Antiaris into oral capsules to mask its bitter taste and reduce bulkiness of the product to improve patients' convenience. In this study, four (4) conventional release capsule formulations were successfully prepared from the decoction via wet granulation using corn starch, lactose, light magnesium carbonate (LMC), and microcrystalline cellulose (MCC) and labelled A01, A02, A03, and A04 respectively. The drug-excipient compatibility studies on A01, A02, A03, and A04 were investigated using Fourier transform infrared (FTIR) spectroscopy. The flow properties of the granules as well as the quality assessment of the formulations such as dissolution, disintegration, uniformity of weight, and assay tests were evaluated using pharmacopoeial and nonpharmacopoeial methods. Appropriate models were used to investigate the difference factor (f1) and similarity factor (f2) of the dissolution profiles of the formulations and Antiaris. From the study, all formulated granules had excellent flow properties with Carr's index from 7.83 to 9.56%, Hausner's ratio from 1.09 to 1.10, and angle of repose from 25.13 to 27.87°. Drug-excipient compatibility studies demonstrated no interaction between extract and used excipients. All formulations passed the uniformity of weight, disintegration, assay, and dissolution tests. Formulation A02 had the highest dissolution efficiency of 100.12%, while A03 recorded the least value of 97.22% in the 1 h dissolution studies. A comparison of their various dissolution profiles, respectively, to that of its decoction demonstrated their similarity, since, in all comparisons, f2 < 15 and f1 > 50. This implies that, any of these four formulations could be a good substitute for Antiaris.